Impacts of Industrial Disharmony on Tertiary Institutions in Nigeria - Gberevbie, Christopher; Okereka, Onofere Princewill; Mukoro, Akpomuvire (Universitas Kuningan, 2024)
The issue of disharmony in Nigerian tertiary institutions has become a significant challenge, affecting academic quality, institutional stability, and national development. This paper examines the various cases and underlying causes of disharmony within Nigerian universities, polytechnics, and colleges of education. Through a critical review of the literature and empirical data, the paper highlights the adverse impacts of disharmony, such as reduced academic productivity, a decline in the quality of graduates, infrastructural decay, and loss of public trust in higher education. The study argues that addressing disharmony requires collaborative efforts between government, management of institutions, staff unions, and students. By promoting inclusivity, strengthening institutional autonomy, and ensuring effective conflict management mechanisms, Nigerian tertiary institutions can foster a more harmonious and productive academic environment.